Comparative feeding kinematics of tropical hylid tadpoles - Venesky, Matthew D.; Rossa-Feres, Denise C. [UNESP]; Nomura, Fausto; De Andrade, Gilda Vasconcellos; Pezzuti, Tiago Leite; De Sousa, Verônica Thiemi Tsutae; Anderson, Christopher V.; Wassersug, Richard J. (The Company of Biologists, 2013)
Anuran larvae, which are otherwise simple in shape, typically have complex keratinized mouthparts (i.e. labial teeth and jaw sheaths) that allow them to graze upon surfaces. The diversity in these structures among species presumably reflects specializations that allow for maximal feeding efficiency on different types of food. However, we lack a general understanding of how these oral structures function during feeding. We used high-speed digital imaging (500 Hz) to observe tadpoles of six species from the anuran family Hylidae grazing on a standardized food-covered substrate. Tadpoles of these species vary in the number of labial tooth rows, belong to two different feeding guilds (benthic and nektonic), and inhabit ponds and streams. We confirmed that the labial teeth in these species serve two functions: anchoring the mouth to the substrate and raking material off of the substrate. In general, tadpoles with a larger maximum gape or those with fewer labial tooth rows opened and closed their mouths slower than tadpoles with smaller gape or more tooth rows. Nektonic feeding tadpoles released each of their tooth rows proportionally earlier in the gape cycle compared with benthic feeding tadpoles. Lastly, we found some support for the idea that deformation of the jaw sheaths during a feeding cycle is predictable based on tadpole feeding guild. Collectively, our data show that anatomical (e.g. number of labial teeth) and ecological features (e.g. feeding guild) of tadpoles significantly influence how tadpoles open and close their mouths during feeding. © 2013. Published by The Company of Biologists Ltd.
Keywords: Anura; Biomechanics; Geometric morphometrics; High-speed digital imaging; Hylidae; Tadpole